Profile of Post-Ischemic Stroke Patients: A Retrospective-Crossectional - Yudawijaya, Agus; Wibhawa, Patria Adri; S., Febriani (Chakra Brahmanda Lentera Institute, 2025)
Background: Stroke remains a major health issue in Indonesia, with ischemic stroke being the most common type. Evidence on the demographic characteristics and risk factors of post-ischemic stroke patients in outpatient settings is still limited, indicating a gap in secondary prevention efforts. This study aimed to describe the profiles of post-ischemic stroke patients treated at the neurology outpatient unit of Dr. Suyoto Hospital between December 2023 and December 2024. Methods: This study employed a retrospective descriptive-analytical design using patient medical records. The study population was all patients with post-ischemic stroke treated in the neurology outpatient clinic during the study period. Inclusion criteria were patients aged ≥18 years with a confirmed diagnosis of ischemic stroke documented in their medical records, while exclusion criteria included incomplete or missing records and concomitant neurodegenerative disorders. A total of 115 patients met the requirements. Data analysis included descriptive univariate statistics and bivariate analysis (Chi-square and Fisher’s exact test) to assess associations between demographic characteristics and risk factors. The study followed the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) guideline for observational research reporting.. Results: The study found that age over 65 years (35.7%), male sex (66.1%), and hypertension (78.3%) were predominant. Other risk factors included obesity (45.2%), total cholesterol above normal (53.9%), LDL cholesterol above normal (66.1%), normal HDL cholesterol (58.3%), normal triglyceride cholesterol (62.6%), hyperglycemia (59.1%), and hyperuricemia (55.7%). Most patients had no prior history of heart disease (65.2%). Conclusion: This study concludes that uncontrolled risk factors in post-ischemic stroke patients, namely hypertension, obesity, elevated total cholesterol, high LDL cholesterol, hyperglycemia, and hyperuricemia, contribute to the risk of recurrent stroke and require more effective outpatient management strategies.